1975
DOI: 10.1039/c39750000923
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of penicillin G fromD- andL-[14C]- and [α-3H]-valine

Abstract: Excellent incorporations of both D-[l-14C]-and L-[ U-14C]-valine into penicillin G by a high producing strain of Pencillium chrysogenum is reported ; the label from ~-[a-~H]-valine is not incorporated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Likewise the antibiotic penicillin has three stereocenters yielding eight possible stereoisomers, yet only the (2 S ,5 R ,6 R )-diastereomer has significant antibacterial activity, and chloramphenicol, an antibiotic for the treatment of meningitis, cholera, and typhoid fever, shows only the ( R , R )-diastereomer is active (Figure ). In addition to compound activity, determining the correct structure, including the correct stereochemistry, is essential in protecting intellectual property and avoiding costly patent disputes. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise the antibiotic penicillin has three stereocenters yielding eight possible stereoisomers, yet only the (2 S ,5 R ,6 R )-diastereomer has significant antibacterial activity, and chloramphenicol, an antibiotic for the treatment of meningitis, cholera, and typhoid fever, shows only the ( R , R )-diastereomer is active (Figure ). In addition to compound activity, determining the correct structure, including the correct stereochemistry, is essential in protecting intellectual property and avoiding costly patent disputes. , …”
Section: Introductionmentioning
confidence: 99%
“…2 In addition to compound activity, determining the correct structure, including the correct stereochemistry, is essential in protecting intellectual property and avoiding costly patent disputes. 3,4 Two powerful technologies for determining the stereochemistry of diastereomers include single crystal X-ray and NMR spectroscopy. While X-ray crystallography can unequivocally establish the stereochemistry of diastereomers, the technology requires sufficient quantity, purity, and solubility of the material as well as the time and resources to grow a diffraction quality crystal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since this tripeptide is accompanied in the mycelium of C. acremonium by a related peptide containing a residue of 8-hydroxyvaline (Loder & Abraham, 1971a), the question arises of whether oxidation at the l-carbon atom of a valine residue precedes closure of the thiazolidine ring. Adriaens et al (1975a) and Bycroft et al (1975) have shown by experiments with DL-[2-3H]valine, 4,valine and D-[2-3H]valine respectively that D-valine is not incorporated directly into penicillin produced by P. chrysogenum, but only after epimerization to L-valine, and that no 3H migration from C-3 to C-2 of the valine occurs during this process. These results are consistent with the synthesis of the LLD tripeptide from L-valine, but not from the D isomer, in C. acremonium (Abraham, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Neither the tritium label from 0-nor that from L- [2-3 H] valine is incorporated into penicillin by P. chrysogenum cells (Bycroft et at., 1975b;Adriaens et at., 1975), suggesting that the o-isomer is not a direct precursor of penicillin. The loss of label from the IX-position of the L-isomer was to be expected with the inversion of configuration in the final product.…”
Section: Incorporation Of Valine and Cyst(e)ine Into Penicillins And mentioning
confidence: 99%